A Generalized Sign Pattern Matrix - G. Gomathi Eswari , Dr.A.Rameshkumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This article is a number of fundamental results are given and various constructions are presented. The sign patterns of symmetric idempotent matrices through order 5 are determined. Sign patterns of idempotent matrices, especially symmetric idempotent matrices are investigated